The Dynamics of Marriage Registration Implementation in the Multiethnic Muslim Community in Pekanbaru City, Riau - Cisilia Maiyori; Muhammad Ahalla Tsauro (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
This study analyzes the dynamics of marriage registration implementation in Pekanbaru City through a juridical-sociological approach. The main focus of the research is to examine the implementation of marriage registration regulations, identify inhibiting factors, and formulate an effective model of approach. The findings reveal that the ambivalence of Article 2 of Law No. 1 of 1974 on Marriage creates legal uncertainty, where society tends to perceive marriage registration merely as an administrative formality rather than as a requirement for the legal validity of marriage in the eyes of the state. The study further reveals the significant impact of unregistered marriages, particularly on the legal protection of women and children. Empirical data show that 45% of divorce cases cannot be formally processed due to the absence of a marriage certificate, while 35% of children from unregistered marriages face difficulties obtaining complete birth certificates. At the implementation level, there is a notable geographical disparity, with the highest compliance rate in Pekanbaru Kota (85%) and the lowest in Rumbai Pesisir (68%). The main inhibiting factors include regulatory, socio-cultural, economic, bureaucratic, and infrastructural aspects. The complexity of procedures, limited digital infrastructure (only 45% of Religious Affairs Offices possess adequate facilities for the SIMKAH system), and weak coordination between Religious Affairs Offices and the Civil Registry Office (with data integration only at 65%) further exacerbate the situation. This study recommends a holistic approach encompassing regulatory reform, infrastructure equalization, bureaucratic simplification, and intensive public outreach through multi-stakeholder collaboration to enhance the effectiveness of marriage registration in Pekanbaru City.